2011
DOI: 10.1007/s12640-011-9251-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre- and Postnatal Manganese Exposure on Brain Histamine Content in a Rodent Model of Parkinson’s Disease

Abstract: Rats lesioned shortly after birth with 6-hydroxydopamine (6-OHDA; 134 μg icv) represent a near-ideal model of severe Parkinson's disease because of the near-total destruction of nigrostriatal dopaminergic fibers. There are scarce data that in Parkinson's disease, activity of the central histaminergic system is increased. The element manganese, an essential cofactor for many enzymatic reactions, itself in toxic amount, replicates some clinical features similar to those of Parkinson's disease. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…In contrast, we found that 6-OHDA induces enhanced tissue levels of histamine in different brain areas. This effect is similar to the results previously reported by other authors in rats [ 19 , 28 ] and patients with Parkinson’s Disease [ 29 , 30 ]. The high tissue content of histamine may contribute to the neuroinflammation process produced by the toxin administration [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, we found that 6-OHDA induces enhanced tissue levels of histamine in different brain areas. This effect is similar to the results previously reported by other authors in rats [ 19 , 28 ] and patients with Parkinson’s Disease [ 29 , 30 ]. The high tissue content of histamine may contribute to the neuroinflammation process produced by the toxin administration [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…It can also be considered as a neurotransmitter because of its accumulation in presynaptic vesicles during excitation, where it is released and interact with some ionotropic receptors such as AMPA kainate, NMDA and GABA receptors [9]. Similarly abnormal concentrations of manganese in the brain, especially in the basal ganglia, are associated with neurological disorders similar to Parkinson's disease [10]. High levels of Mn in blood can cause the compulsive behavior emotional liability and hallucinations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report the aftereffects (e.g., reduced intellectual function) of Mn exposure on children at various developmental stages (Woolf et al 2002 ; Wasserman et al 2006 ). Mn crosses the placenta to impair embryonic development (Spencer 1999 ) and produce behavioral abnormalities through childhood and into adulthood (Kwieciński and Nowak 2009 ; Nowak et al 2010 , 2011 ; Brus et al 2012 ; Szkilnik et al 2014 ). It is evident that Mn in excess is toxic to human embryos and fetuses (Colomina et al 1996 ).…”
Section: Introductionmentioning
confidence: 99%